Menanamkan Moral Pada Anak Melalui Metode Bercerita - Hazhira Qudsyi (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2013)
Children are the future generation. In the hands of children that the future of this nation are, so the children are the most valuable heritage that must be guarded carefully. But in fact, there are many reported cases of crime committed by children themselves. This suggests looking increasingly less moral values held by a child during its development. Daradjat (1977) explains that moral decline is not only experienced by adults only, but also the moral decline has spread to the young people, children and adolescents. Therefore, it is understood that it is important to provide moral education from an early age in children. However, teach and instill morals in children is not an easy matter. Moral is a concept that tends to the abstract, given moral is talk about the values that are abstract concepts. Basically, an abstract concept that is not easily understood by children who have a tendency to think things concretely. Therefore it takes a certain techniques and methods that can be done in introducing and instill morals in children, one of which is story telling. Conclusion, to introduce and instill moral values in children can be done by using the method of story telling in the delivery process, so that children find it easier to understand moral concepts. The efforts can be made for story telling method can be optimal in giving an understanding of moral values in children, namely with the development of methods of story telling, considering the characteristics of listeners, and view messages in the story.Keywords: moral reasoning, children, story telling